Effect of Tackifying Resins on Composite Propellant Formulations - Bagguley, Emily (Cranfield University, 2018)
Poster presented at the 2018 Defence and Security Doctoral Symposium.Composite propellants consist of solid filler particles suspended in a polymeric matrix. In order to achieve maximum performance the amount of solid filler is increased resulting in a viscous suspension. Such high viscosities present processing challenges during manufacture, as such the following work utilises ResonantAcoustic© Mixing, a novel mixing method able to handle such highly viscous materials.In composite propellants, the most common polymer chosen is hydroxyl-terminated polybutadiene (HTPB) for its excellent mechanical properties as well as its potential for high solids loading. Once cured HTPB provides an intricate polymeric solid matrix in which solid particles may be suspended.Tackifying resins have been commonly utilised in the adhesive industry, but rarely, if ever, in propellants. This work utilises tackifying resins to modify HTPB and use these resin-modified HTPBs to produce composite propellant formulations. Functionally the resins are used to increase adhesion between the binder and the filler; potentially allowing formulators to remove common processing aids such as bonding agents and plasticisers. This work investigates the mechanical and rheological effect of such modifications.
Keywords: 'Composite propellants'; 'Rheology'; 'Tackifying resins'; 'DSDS18 poster'; 'DSDS18'; 'Polymers and Plastics'